(untitled) - Anon, Ellen (Hoboken, N.J., 2007)
In the new edition of this practical guide, master photographer Ellen Anon and digital-imaging expert Tim Grey show you how to capture the beauty of nature by shooting the best possible photos from the start—and then getting the most out of your images at your desktop. You’ll find eye-opening techniques, workflow ideas, and terrific Photoshop tools, plus a host of valuable tips and stunning examples from some of the most esteemed professional nature photographers working today.
Keywords: Nature photography,Adobe Photoshop,Nhiễm ảnh thiên nhiên